The therapeutic efficacy of radical resection for hepatocellular carcinoma varies markedly by tumor location: a retrospective real-world study - Feng, Xu; Wei, Yi-Qiu; Liu, Jia-Rui; Shi, Zheng-Rong; Chen, Kai; Lv, Yong-Shuang (Frontiers in Pharmacology, 2025)
AimThis study aims to explore the impact of the distance between the tumor and the main trunk or first branch of the portal vein on the prognosis of hepatocellular carcinoma (HCC) patients undergoing radical resection.MethodsThis study retrospectively evaluated HCC patients who underwent radical resection between 1 January 2018 and 30 September 2024. Tumors were classified into two categories based on their location: central tumors and peripheral tumors. Central tumors were defined as those located within 2 cm of the main trunk or first branch of the portal vein, while the remaining tumors were classified as peripheral tumors. Recurrence-free survival (RFS) and overall survival (OS) were compared between the two groups. Univariate and multivariate COX analyses were conducted to identify factors associated with RFS and OS. Propensity score matching (PSM) was employed to eliminate intergroup differences for further validation.ResultsA total of 667 HCC patients undergoing radical resection were initially enrolled. Through PSM, 247 patients were successfully matched in each comparative group. In the PSM cohort, the median RFS (mRFS) for patients with central tumors was 23.00 months (95% CI, 18.01–27.99 months), while the mRFS for those with peripheral tumors was 30.50 months (95% CI, 26.17–34.83 months) (p = 0.004). The median OS was 56.00 months (95% CI, 52.10–59.90 months) for central tumors and 72.00 months (95% CI, 67.37–76.63 months) for peripheral tumors (p = 0.043). Multivariate COX analysis confirmed that the distance of less than 2 cm between the tumor and the main trunk or first branch of the portal vein was an independent risk factor for RFS and OS in patients undergoing radical resection for HCC (HR: 1.744, p < 0.001; 1.728, p < 0.001, respectively).ConclusionThe distance between the tumor and the main portal vein trunk or first branch correlates with the prognosis of hepatocellular carcinoma patients undergoing radical resection.